C-Reactive Protein Levels in Preeclampsia Singleton Pregnant Women and Their Outcomes - Umbreen Fatima, Abdullah Shamshad, Hafiz Muhammad Qamer, Maria Dhahri, Muhammad Faheem Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Preeclampsia is a hypertensive disorder that occurs during pregnancy, typically after 20 weeks of gestation and the relationship between C-reactive protein levels and adverse pregnancy outcomes. Objective: To analyze the C-reactive protein levels in preeclampsia singleton pregnant women and their outcomes. Methodology: This case control study was performed at District Health Development Centre, Sahiwal from 1st October 2022 to 31st March 2023. A total of 100 women including 50 preeclampsia and 50 controls were enrolled after the ethical clearance of the study. The inclusion criteria consisted of women having singleton pregnancy and were clinically diagnosed to be suffering from preeclampsia. Participants were assessed clinically, biochemically, and via ultrasonography to confirm a normal pregnancy or diagnose preeclampsia. The association between C-reactive protein levels and preeclampsia was then evaluated. The outcomes of pregnancy with preeclampsia and high C-reactive proteins were followed upto 3 days in women after delivery. Results: The maternal mean age was almost similar within both groups as 24.32±4.1 years and 25.26±5.63 years respectively. There was a higher body mass index trend in preeclampsia women than controls (p<0.05). The mean systolic blood pressure and diastolic blood pressure was much higher than control with a mean value as 115.33±9.39 vs 72±7.74 respectively. There were 72% of the preeclampsia vs 15% controls having previous history of hypertension. While only 16% preeclampsia and 10% control was already presenting a clinical history of diabetes. The mean preeclampsia C-reactive protein levels was 6.25±2.8 mg/L ad that of controls was 3.1±1.3 mg/L with 70% cases in preeclampsia group having higher that 15.5 mg/L CRP level in comparison to only 30% controls. The 35(70%) women having high C-reactive protein level and were preeclampsia; had adverse outcomes of their pregnancy including low birth weight in 77.1 (n=27) cases while preterm birth in 62.85 (n=22) cases. Conclusion: Higher levels of C-reactive proteins were linked with preeclampsia in singleton pregnant women leading to adverse outcomes of pregnancy including delivery complications, low birth weight and preterm births in significant number of cases. Keywords: C-reactive protein, Preeclampsia, Pregnant women, Outcome